APPLYING LITERACY STRATEGIES IN LEARNING INTEGRATIVE THEMATIC IN STATE PRIMARY SCHOOL 14 BANDA ACEH - Aulia Maharani; Nur Alifa Illa; Ildha; Siti Mayang Sari; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses descriptive qualitative research methods, namelyresearch based on phenomena observed by researchers in accordance withevents that occurred at State Primary School 14 Banda Aceh. Based on existingphenomena, the researcher concluded that the learning carried out by teachersat State Primary School 14 Banda Aceh did not fully use the independentcurriculum due to inadequate facilities and physical conditions so that theindependent curriculum was only implemented in classes I and IV. From theresults of the researcher's observations, it was found that the special strategiesused by teachers in the learning process had an effect on student literacy.Regarding this, teachers apply literacy strategies which are carried out everyTuesday to get used to reading in the school field. In addition, students arerequired to take part in reading activities in class before learning begins. Aftercarrying out the reading activity, the student representative comes forward infront of the other students to tell what he has read. This activity provides anincrease in students' reading literacy by enjoying reading. Students will alsoobtain some information from the books they have read. Based on the resultsof an interview with one of the teachers, namely a grade 5 teacher, that in orderfor thematic learning to run well, the teacher makes lesson plans that areadapted to several themes in one lesson. Apart from lesson plans, things thatneed to be considered so that thematic learning runs well are teaching materials,learning media, LKPD and other learning tools.